MARKETING MANAGEMENT OF THE ACTIVITIES OF DOMESTIC ECONOMIC ENTITIES IN THE TOURIST SERVICES MARKET OF UKRAINE - DYBCHUK, LIUDMYLA; HOLOVCHUK, YULIIA; PCHELIANSKA, GALYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is devoted to the problems of marketing strategy and activity of the tourist enterprise. In the context of the coronavirus infection pandemic, significant changes are taking place in the tourism industry. Adequate response of tourism enterprises to possible changes in data through marketing tools, a key element in modern conditions is - the creation of a sustainable brand and the use of marketing support tools. The article analyzes the relationship between these problems. As a result of the study, the authors identified the main trends, conditions of the tourism market and the generalized consequences of the pandemic: new attributes of travel, changes in the activities of tour operators, new technological solutions. Features of the market of tourist services are characterized. It is determined that an important problem that limits the possibilities of the fullest use of the entrepreneurial potential of tourism organizations is the insufficient level of strategically-oriented marketing justifications in the management decisions. The urgency of the research topic necessitated the improvement of management systems of business structures of various profiles and, in particular, operating in the market of tourist services, which retain a high potential for development in a crisis situation. One of the main areas of such improvement is to increase the level of marketing support of the management process with its ability to initiate significant business effects.